Exploring climatic resilience through genetic improvement for food and income crops - Chiona, M.; Chigeza, G.; Ntawuruhunga, Pheneas (Elsevier, 2017)
Plant breeding has been one of the main drivers of crop yield gains during the past century. Breeding for yield improvement through resistance to pests and diseases and chemico-physical constraints to crop production has contributed immensely to food security, nutrition, and improved incomes across Africa. Achievements through breeding have not been evenly spread across the entire range of crops grown in southern Africa. In addition, in some locations climate change threatens to reverse some of the gains from improved crop cultivars. The aim of this chapter is to analyze the progress made to date through breeding and to put forward models, which will enable farmers to benefit from breeding products both developed in the recent past and future products in the various breeding pipelines. Breeding for multiple stresses has been improved through molecular breeding techniques; however, the results are yet to benefit smallholder farmers who are the intended beneficiaries and the end users. Drought and extreme temperature-tolerant cultivars have higher chances of sustaining crop production in southern Africa. Reducing bureaucracies in seed release and moving beyond research-biased participatory varietal selection methods are two steps that require enhancement to improve and increase adoption rate of new breeding products.